2019
DOI: 10.1155/2019/8163591
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis and Variation in Predicted Functions of the Granulation Tissue Microbiome in HPV Positive and Negative Severe Chronic Periodontitis

Abstract: Retrospective analysis has already shown correlation between severe Chronic Periodontitis (CP) cases with human papiloma virus (HPV). Hence, we aimed to explore deep-seated infected granulation tissue removed during periodontal flap surgery procedures for residential bacterial species between HPV+ and HVP- CP cases, which may serve as good predisposition marker for oral cancer. All CP-granulation samples showed the prominence of Firmicutes, Proteobacteria, and Bacteroidetes phyla with an abundance of gram nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…16S ribosomal RNA analysis of bacterial flora revealed that HPV infection was associated with higher abundances of Haemophilus and Peptostreptococcus genera in the cervix and Selenomonas species in the mouth 28 . Capnocytophaga ochracea was more abundant in HPV‐positive severe chronic periodontitis cases than in HPV‐negative cases 29 . In our previous study, Actinomyces , Veillonella, and Prevotella genera were more frequently detected in individuals with high HPV16 viral copy numbers than in those with low HPV16 viral copy numbers 30 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…16S ribosomal RNA analysis of bacterial flora revealed that HPV infection was associated with higher abundances of Haemophilus and Peptostreptococcus genera in the cervix and Selenomonas species in the mouth 28 . Capnocytophaga ochracea was more abundant in HPV‐positive severe chronic periodontitis cases than in HPV‐negative cases 29 . In our previous study, Actinomyces , Veillonella, and Prevotella genera were more frequently detected in individuals with high HPV16 viral copy numbers than in those with low HPV16 viral copy numbers 30 .…”
Section: Discussionmentioning
confidence: 67%
“…28 Capnocytophaga ochracea was more abundant in HPV-positive severe chronic periodontitis cases than in HPVnegative cases. 29 In our previous study, Actinomyces, Veillonella, and Prevotella genera were more frequently detected in individuals with high HPV16 viral copy numbers than in those with low HPV16 viral copy numbers. 30 Thus, the oral cavity may be a model of bacterial and HPV interaction.…”
Section: Discussionmentioning
confidence: 78%
“…The above functional could explain the ndings of the present study that higher R.Mucilaginosa in esophageal cancerous tissue than that in para-cancerous. Another differential bacterium, P.Endodontalis, was dominantly associated with oral diseases [23]. Interestingly, P.Endodontalis was the most representative taxa which were abundant in gastric adenocarcinoma microbiome [24].…”
Section: Discussionmentioning
confidence: 99%
“…only in HIV patients with gingivitis. Similarly, a combination of C. ochracea and HPV virus has only been observed in patients with periodontitis (Chowdhry, 2019, Ganly, 2019. Capnocytophaga spp.…”
Section: Systemic Pathologiesmentioning
confidence: 99%
“…The presence of mucositis and gingivitis is often associated with these diseases and their treatment (Vesty et al, 2019), which could induce dysbiosis, conducive to the growth of Capnocytophaga spp. In a comparison of HPV + and HPVcases, Chowdhry et al (Chowdhry et al, 2019) demonstrated dominance of C. ochracea. At the same time, the mismatch repair pathway and nucleotide excision repair were altered in the HPV + samples, suggesting greater formation of DNA adducts, which can lead to the process of carcinogenesis.…”
Section: Accepted Articlementioning
confidence: 99%